A randomized cross-over study of the quality of cardiopulmonary resuscitation among females performing 30:2 and hands-only cardiopulmonary resuscitation - Patrickson W Clive; Potts Jerald; Ricard Mark D; Parekh Jesal N; Trowbridge Cynthia; Cason Carolyn L (BMC, 2009)
Abstract Background Hands-Only cardiopulmonary resuscitation (CPR) is recommended for use on adult victims of witnessed out-of-hospital (OOH) sudden cardiac arrest or in instances where rescuers cannot perform ventilations while maintaining minimally interrupted quality compressions. Promotion of Hands-Only CPR should improve the incidence of bystander CPR and, subsequently, survival from OOH cardiac arrest; but, little is known about a rescuer's ability to deliver continuous chest compressions of adequate rate and depth for periods typical of emergency services response time. This study evaluated chest compression rate and depth as subjects performed Hands-Only CPR for 10 minutes. For comparison purposes, each also performed chest compressions with ventilations (30:2) CPR. It also evaluated fatigue and changes in body biomechanics associated with each type of CPR. Methods Twenty healthy female volunteers certified in basic life support performed Hands-Only CPR and 30:2 CPR on a manikin. A mixed model repeated measures cross-over design evaluated chest compression rate and depth, changes in fatigue (chest compression force, perceived exertion, and blood lactate level), and changes in electromyography and joint kinetics and kinematics. Results All subjects completed 10 minutes of 30:2 CPR; but, only 17 completed 10 minutes of Hands-Only CPR. Rate, average depth, percentage at least 38 millimeters deep, and force of compressions were significantly lower in Hands-Only CPR than in 30:2 CPR. Rates were maintained; but, compression depth and force declined significantly from beginning to end CPR with most decrement occurring in the first two minutes. Perceived effort and joint torque changes were significantly greater in Hands-Only CPR. Performance was not influenced by age. Conclusion Hands-Only CPR required greater effort and was harder to sustain than 30:2 CPR. It is not known whether the observed greater decrement in chest compression depth associated with Hands-Only CPR would offset the potential physiological benefit of having fewer interruptions in compressions during an actual resuscitation. The dramatic decrease in compression depth in the first two minutes reinforces current recommendations that rescuers take turns performing compressions, switching every two minutes or less. Further study is recommended to determine the impact of real-time feedback and dispatcher coaching on rescuer performance.